Effect of Fixed Asset Turn Over, Return on Net Worth, Plowback Ratio And Inventory to Net Working Capital - Amalia, Tasya; Hariyanto, Dedi (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
This research aims to determine the influence of Fixed Asset Turn Over, Return On Net Worth, Plowback Ratio and Inventory To Net Working Capital on Profit Growth of Energy Sector Companies Listed on the IDX in 2020-2022. The type of research used is associative. The population in this study was 75 companies with a sample of 51 companies using purposive sampling techniques. The analysis techniques used in this research are classical assumption tests and statistical tests. Based on the results of the classical assumption test, it is stated that the data is normally distributed, there are no symptoms of multicollinearity, there is no heteroscedasticity, there is no auto correlation, and the data is linear. The results of the simultaneous influence test (F Test) show that the Fixed Asset Turn Over, Return On Net Worth, Plowback Ratio and Inventory To Net Working Capital variables show that the independent variables together do not have a significant effect on the dependent variable, namely profit growth. The results of the partial influence test (t test) show that Fixed Asset Turn Over, Return On Net Worth, Plowback Ratio and Inventory To Net Working Capital do not have a significant influence on profit growth.